Correlation between Eruption of Permanent Teeth and Anthropometric Measurements among School Children - Daniel Rajendran T (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The assessment of nutritional status of a child is essential in the clinical practice. Several clinical and laboratory parameters are being used for this purpose, of which height and weight play a major role. This study was carried out to correlate the eruption of permanent teeth with anthropometric measurements among school children. Method: This cross sectional study was carried out among 983 school children between the age group of 4-14 years. The height and weight were measured using standardized scales. Eruption of permanent teeth were examined clinically. The classification of stunting and underweight was carried out based on CDC standards. Results: Stunting was present in around 10% of each age group upto 7 years, followed by 20-30% between 7-8.9 years. From 9-11 years, stunting was present in around 40% of the participants and beyond 10 year, it was present in around 50% of the participants. Conclusion: Although this study has not demonstrated statistical significance, it has elucidated the increased prevalence of malnutrition with advances in age with respect to both stunting and underweight, warranting adequate addressing of the nutritional needs of the school children.